Evaluation of major nutritional components and phytochemical screening of four different Bangladeshi branded unifloral honey and their brine shrimp toxicity study - Hasan, Md. Mahmodul; Islam, Md.Jahirul; Sarkar, Subodh Kumar; Absar, Nurul (International Journal of Biological Research, 2016)
The research work was conducted to investigate the biochemical composition of four different Bangladeshi branded unifloral honey. The honey from Litchi (Litchi chinensis), Black cumin (Nigella sativa), Coriander (Coriandrum sativum), Mustard (Brassica campestris) were used. We investigated color, pH, Moisture, Dry matter ,Specific gravity, Total sugar, Reducing sugar, Non reducing sugar, Crude protein, Water soluble protein, Lipid, Ash, Total Carbohydrate, Metabolizable energy, Vitamin C and minerals content. The result revealed the presence of nutrient constituent among the varieties comprising pH(3.47 to 4.06),specific gravity(1.32 to 1.37),dry matter(85.2 to 86.6%), moisture(13.4 to 14.7%),ash(0.64 to 0.66%),lipid(0.14 to 0.16%),crude protein(0.63 to 0.73%), total carbohydrate(83.70 to 85.18%), metabolizing energy(2763.59 to 2808.95Kcal/Kg),total sugar(77.36 to 81.2%),reducing sugar(60.5 to 63.03%),non-reducing sugar(16.61 to 18.17%),vitamin C (4.63 to 6.36mg%), and minerals such as Calcium(6.36 to 7.87mg%) and Iron(1.62 to 1.89mg%) respectively. Moreover, alkaloids, flavonoids found in all varieties but only polyphenols was absent in Black cumin varieties. In the cytotoxic activity studies, LC50 values were obtained in the range of 4800 to 4966.7Âµg/ml.